Функція анжамбеману в драматичних творах Лесі Українки (на прикладі драматичної поеми «Одержима») - Кицан, Олена; Kytsan, Olena (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто особливий стилістичний прийом анжамбеман, який слугує сильним засобом інтонаційного виділення перенесених відрізків фрази. Він також свідчить про віршову структуру драматичного тексту і сприяє збою ритму. У творчості Лесі Українки анажамбеман завжди виправданий і має певний сенс, надає твору драматизму, напруги. У статті показано своєрідність перенесень у драматичній поемі «Одержима», проаналізовано їхні різні типи. Окрім того, визначено загальну частотність анжамбеману за методикою, що її розробила С. Матяш. У драматичній поемі «Одержима» прийом анжамбеману виконує низку важливих функцій, зокрема композиційну, графічну, стилістич- ну, експресивно-виражальну тощо. The special stylistic device of the enjambement is examined in the article, which serves as a strong tool of the intonational highlighting the phrase segments cut off by the verse section. It also signals about the verse structure of dramatic text and causes the failure of rhythm. In the works of Lesia Ukrainka the enjambement as an effective poetic figure is not a goal in itself, a device for a device. It is always justified and carries certain sense, gives dramatic effect, some tension to the tekst. The intonation has a dominant role in dramatic works. It allows to pass expression, change of mood, experiencing. Еnjambement is just one of the strongest device s of intonation’s transmission. In the article the originality of transferences in the dramatic poem “Oderzhyma” is rotined, their different types are analysed. Moreover, general frequency of enjambement is defined after a method, developed by S. Matіash. In the dramatic poem “Oderzhyma” the device of enjambement executes important functions, such as composition, graphic, stylistic, expressive and others
The Function of the Enjambement in the Dramatic Works of Lesia Ukrainka (on the Example of the Dramatic Poem “Oderzhyma”)
Keywords: анжамбеман; ритм; стилістичний прийом; поезія; література; функція; драматургія; enjambement; rhythm; stylistic device; literature; poetry; function; dramaturgy